Pengaruh Marketing Mix (7P) Terhadap Repurchase Intention (Minat Beli Ulang) Survei Pada Omad Coffee di Kota Medan - Anggita Rizkia; Tuti Anggraini; Siti Aisyah (Nirta Learning Centre, 2025)
This study aims to determine the effect of product, price, place, promotion, process, people, and physical evidence (Marketing Mix 7P) on purchasing interest in Omad Coffee Medan consumers. This study uses a quantitative method. Data collection was carried out using questionnaires, observation and library research. The number of respondents used was 100 respondents who were consumers of Omad Coffee in Medan City. The analysis technique in this study used Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results of this study indicate that the variables of product, price, place, and physical form have a significant positive effect on repurchase interest while promotion, process and people do not produce a significant effect on repurchase decisions in Omad Coffee consumers in Medan City.